2018
DOI: 10.1016/j.tranon.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Anatomical and Functional Imaging of Orthotopic Glioblastoma Development and Therapy using Multispectral Optoacoustic Tomography

Abstract: PURPOSE: Here we demonstrate the potential of multispectral optoacoustic tomography (MSOT), a new non-invasive structural and functional imaging modality, to track the growth and changes in blood oxygen saturation (sO2) in orthotopic glioblastoma (GBMs) and the surrounding brain tissues upon administration of a vascular disruptive agent (VDA). METHODS: Nude mice injected with U87MG tumor cells were longitudinally monitored for the development of orthotopic GBMs up to 15 days and observed for changes in sO2 upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…This is also available on the iThera Acuity system, which is designed for larger animals and human investigations. Several studies have reported dynamic vascular response of tumors in mice or rats to vascular disruption caused by CA4P, CA1P and EPC2407 [ 92 , 118 , 119 , 130 , 239 , 240 ]. In most cases, changes in [HbO 2 ] and [Hb] are examined, thereby also revealing vascular oxygen saturation (sO 2 ).…”
Section: Imaging Technologiesmentioning
confidence: 99%
“…This is also available on the iThera Acuity system, which is designed for larger animals and human investigations. Several studies have reported dynamic vascular response of tumors in mice or rats to vascular disruption caused by CA4P, CA1P and EPC2407 [ 92 , 118 , 119 , 130 , 239 , 240 ]. In most cases, changes in [HbO 2 ] and [Hb] are examined, thereby also revealing vascular oxygen saturation (sO 2 ).…”
Section: Imaging Technologiesmentioning
confidence: 99%
“…Volumetric imaging of glioblastoma in nude mice was demonstrated without contrast agents by exploiting differential contrast under illumination with 800 and 850 nm. The authors also quantified tumor O 2 saturation, which increased 15 days after inoculation, whereas the tissue became hypoxic 42 days after inoculation (Balasundaram et al, 2018). In another study, integrin expressing tumor cells were tagged with an IRDye800-based contrast agent while also assessing tumor SO 2 , which was 13% lower than in healthy brain tissue (Li M. et al, 2008).…”
Section: Tumorsmentioning
confidence: 99%
“…This is also available on the iThera Acuity system, which is designed for larger animals and human investigations. Several studies have reported dynamic vascular response of tumors in mice or rats to vascular disruption caused by CA4P, CA1P and EPC2407 [92,117,118,129,229,230]. In most cases, changes in [HbO2] and [Hb] are examined, thereby also revealing vascular oxygen saturation (sO2).…”
Section: Photoacoustics-multispectral Optoacoustic Tomography (Msot)mentioning
confidence: 99%